STRATEGIC SOURCING MANAGEMENT: a solution in behavior changes with the Impact of the Sugar-Energy Sector on Covid-19 - Revoredo, Daniel Donizeti; Regattieri, Carlos Roberto (Revista Interface Tecnológica, 2022)
Changes in behavior with the Impact of the Covid-19 Pandemic on the sugar-energy sector have been the subject of great discussions, since problems arising from this context bring great challenges both to the economy of the sector and also to the companies in which it operates. Thus, the search for methods and studies to remain in the market and guarantee its competitiveness, the Strategic Purchasing Management tool has contributed with significantly positive results in this sector. This aims to discuss and provide information on the proposed topic. The methodology used was the literature review, where books were consulted that brought the subject chosen for this study by renowned authors in the area. We seek to demonstrate the pandemic scenario in the sugar-energy sector, the importance of the purchasing sector in times of crisis and representativeness of the purchase volume. This work sought to demonstrate the importance of Strategic Sourcing Management in the business environment, which has become fundamental for the economic-financial efficiency of the business in times of crisis.
Keywords: Strategic Sourcing Management; Planning; Sugar-energy; Covid-19